Systematic Rearrangement of Korean Scirpus L. s.l. (Cyperaceae) as Inferred from Nuclear ITS and Chloroplast rbcL Sequences - Jung, J.D., Ajou University, Suwon, Republic of Korea; Choi, H.K., Ajou University, Suwon, Republic of Korea (Journal of plant biology = Singmul Hakhoe chi, 2010)
The genus Scirpus L. s.l. (Cyperaceae) has been accepted as a polyphyletic taxon by most plant taxonomists. This genus was separated into different genera by several different authors: Scirpus s. str., Trichophorum Pers., Bolboschoenus (Asch.) Palla, Schoenoplectus (Rchb.) Palla, and Schoenoplectiella Lye. The heterogeneity of Korean Scirpus s.l. has not yet been studied. We examined 17 taxa of Korean Scirpus s.l. by morphological characters and phylogenetic analyses based on nuclear ITS and chloroplast rbcL sequences. Phylogenetic analyses using maximum parsimony, maximum likelihood, and Bayesian method provided sufficient resolution. The phylogeny revealed the polyphyly of Korean Scirpus s.l. with five distinct clades. These clades correspond to Bolboschoenus, Schoenoplectus s.str., and Schoenoplectiella, Scirpus s.str., and Trichophorum, respectively. These five genera were delimited in terms of the morphology of tuber, bract, and inflorescence. By virtue of our findings, we suggest that the 17 taxa of Korean Scirpus s.l. should be placed into five genera as follows: Bolboschoenus (two species), Schoenoplectus (three species), Schoenoplectiella (six species), Scirpus s.str. (five species), and Trichophorum (one species).